The Influence of Fraction Puzzle Media on the Mathematical Concept Understanding Ability of Elementary School Students - Syarifah , Ahda; Suryaningsih, Tri; Widiyanto, Rohmat (Universitas Islam Lamongan, 2025)
This research aims to determine the effect of fraction puzzle media on students' ability to understand mathematical concepts. This research was conducted at SDN Petir 04 in class III, the second semester of the 2023/2024 academic year. The research method used is quasi-experimental with a nonequivalent control group design. The research samples in this study were class III-B students as the experimental class and class III-C students as the control class, which were obtained using cluster random sampling techniques. The test given is an essay with seven questions. The statistical analysis using the Independent Sample T-test showed a significance value of 0.000 < 0.05, leading to the rejection of H0 and acceptance of H1. This confirms that students in the experimental class, who were taught using fraction puzzle media, demonstrated better conceptual understanding than those in the control class, who received conventional instruction. The fraction puzzle media enhances learning by providing a hands-on, interactive experience that helps students visualize and manipulate fraction concepts more effectively. This approach facilitates deeper comprehension, reduces misconceptions, and improves problem-solving skills related to fractions. Therefore, integrating fraction puzzle media into mathematics instruction can effectively enhance students’ conceptual understanding and engagement in learning fractions.